Learning Materials of Concept Attainment Model with Concept Mapping Techniques to Improve Students’ Creative Thinking Skills and Concept Mastery - Putri Nanda Agustin; Nadi Suprapto; Sunu Kuntjoro (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This research describes the validity of learning materials consisting of the syllabus, lesson plans, handouts, student worksheets, assessment of creative thinking skills, and concept mastery. The method is a modified research and development method, and this research is only limited to the validity of the learning materials. The developed learning materials were tested on 18 grade ten of Senior High School students. The data collection was carried out using the validation methods, and data analysis was carried out quantitatively. The validation results by three validators concluded that the syllabus obtained an average score of 3.81 with a completely valid category, lesson plan obtained an average score of 3.87 with a completely vali category. Meanwhile, handouts obtained an average score of 3.78 with a completely valid category, student worksheets obtained an average score of 3.88 with a completely valid category, assessment of creative thinking obtained an average score of 3.83 with a completely valid category, and assessment of concept mastery obtained an average score of 3.77 with a completely valid category. So that the learning materials developed is declared valid.